Perencanaan program ibu care posyandu turry melalui peer support group - Ramadani, Nurul Ma'rifa; Makmur, Nindha Aulia; Faradiana, Dwi Nur; Gustia, Wanda; Anggraeni, Diva Nabilah; Rahmayanti, Desy Anugerah; Rahayu, Agustin Putri; Permana, Lies; Rohmah, Nur; Nurrachmawati, Annisa; Feriyanti, Alma; Fikri, Mohammad (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Posyandu (Integrated Health Post) is a community-based health service that plays a crucial role in improving maternal and child health. However, at Posyandu Turry, there is still a lack of understanding and participation from mothers, which impacts the effectiveness of Posyandu services. Purpose: To identify problems at Posyandu Turry, prioritize problems using ultrasound methods, and plan an empowerment program that can increase community knowledge and participation in Posyandu activities on an ongoing basis. Method: This study identified problems at the Turry Integrated Health Post (Posyandu), determined priorities using the USG method, and developed an empowerment program using a qualitative case study approach and Participatory Action Research (PAR). Data were collected through interviews, focus group discussions (FGDs), observations, and document analysis. Results: The FGDs revealed that low community knowledge about the importance of Posyandu was the highest-scoring problem. This was due to limited access to information and a lack of engaging educational materials. Based on these findings, the "Ibu Care Posyandu" empowerment program was formulated to increase community knowledge and engagement through easier-to-understand education and consistent information delivery. Conclusions: Low community knowledge, minimal participation by mothers of toddlers, and limited skills of cadres contributed to the low effectiveness of the Turry Integrated Health Post (Posyandu) service. Through case studies and Participatory Action Research (PAR), these problems were collaboratively addressed through the development of a peer-support-based "Ibu Care Posyandu" program to increase community knowledge and engagement.   Keywords: Community Empowerment; Health Education; Maternal Health; Participation; Posyandu.   Pendahuluan: Posyandu adalah layanan kesehatan yang didasarkan pada komunitas dan memiliki peran krusial dalam meningkatkan kesehatan ibu dan anak. Namun di Posyandu Turry masih terdapat rendahnya pemahaman dan partisipasi dari ibu-ibu yang berdampak pada efektivitas pelayanan posyandu. Tujuan: Untuk mengidentifikasi permasalahan di Posyandu Turry, menetapkan prioritas masalah menggunakan metode USG, serta merencanakan program pemberdayaan yang dapat meningkatkan pengetahuan dan partisipasi masyarakat dalam kegiatan posyandu secara berkelanjutan. Metode: Penelitian ini mengidentifikasi masalah di Posyandu Turry, menentukan prioritas dengan metode USG, dan menyusun program pemberdayaan melalui pendekatan kualitatif studi kasus, serta Participatory Action Research (PAR). Data dikumpulkan melalui wawancara, FGD, observasi, dan dokumen. Hasil: FGD menunjukkan rendahnya pengetahuan masyarakat tentang pentingnya posyandu menjadi masalah dengan skor tertinggi. Faktor penyebabnya adalah kurangnya akses informasi dan minimnya materi edukasi yang menarik. Berdasarkan temuan tersebut, dirumuskan program pemberdayaan “Ibu Care Posyandu” untuk meningkatkan pengetahuan dan keterlibatan masyarakat melalui edukasi yang lebih mudah dipahami dan penyampaian informasi yang konsisten. Simpulan: Rendahnya pengetahuan masyarakat, minimnya partisipasi ibu balita, dan keterbatasan keterampilan kader menyebabkan rendahnya efektivitas pelayanan Posyandu Turry. Melalui studi kasus dan Participatory Action Research (PAR), masalah tersebut diatasi secara kolaboratif melalui pengembangan program “Ibu Care Posyandu” berbasis dukungan sebaya untuk meningkatkan pengetahuan dan keterlibatan masyarakat.   Kata Kunci: Edukasi Kesehatan; Kesehatan Ibu; Partisipasi; Pemberdayaan Masyarakat; Posyandu.